I love Lucy. The sixth season [videorecording (DVD)] - Ball, Lucille, 1911-1989; Arnaz, Desi, 1917-1986; Frawley, William, 1887-1966; Vance, Vivian; Asher, William, 1921-2012; Davis, Madelyn Pugh; Kern, James V., 1909-1966; Carroll, Bob, Jr., 1918-2007; Oppenheimer, Jess; Oppenheimer, Jess (CBS Broadcasting Inc., 2015)
Season six sees the Ricardos longing for a less hectic life in the country, so they make plans to move to rural Connecticut, but not before Lucy leaves the Big Apple reeling with some riotous escapades. Includes all 27 episodes.